Magnesium-based alloys analyses by nuclear techniques - Caio Almeida Justino Silva; Lilian Ninoska Muriel; Jesualdo Luiz Rossi; Marcos Antônio Scapin; Isolda Costa; Mitiko Saiki (Brazilian Journal of Radiation Sciences)
Magnesium-based alloys have been proposed for used in temporary biomaterials in the applications that request their biocompatibility and degradability. Analyses of these alloys are of great interest to verify if their element composition is within the product specification and also to evaluate the impurities that may cause toxic effects to the human health or influence in their corrosion processes. In this study, nuclear techniques of neutron activation analysis (NAA) and wavelength dispersive X ray fluorescence spectrometry (WD XRFS) were applied in the analyses of two magnesium-based alloys: commercially pure magnesium (CP-Mg) and AZ31 alloy. The NAA procedure consisted of irradiating aliquots of sample and synthetic element standards followed by measurements using a HGe detector and the WD XFRS was carried out using the Model RIX 3000 X-ray spectrometer. In the CP-Mg sample several element impurities were quantified. In the AZ31 alloy, the alloying element mass fractions were within the product specification and the impurities of As, La, Na and Sb were also quantified. Nickel and sulfur were quantified only by WD XFRS. The Horwitz method was a good parameter to evaluate the repeatability of the results in Al, Mg, Mn and Zn determinations. In conclusion, the results indicated the viability of using NAA and WD XFRS in the analyses of magnesium-based materials mainly due its multielement determinations, precision of the results, quantification of elements in a wide range of mass fractions and the lack of need for sample dissolution.